Impact of Ankylosing Spondylitis on Paitents Work Status, Functional Disability and Quality of Life - A Review - Islam, Mohammad Tanvir; Chowdhury, Minhaj Rahim; Snigdha, Kaniz Shahali Reza; Bhuiyan, Mohammed Saiful Islam (BIRDEM Medical Journal, 2014)
Ankylosing Spondylitis (AS) is a chronic inflammatory rheumatic disease principally affecting the axial skeleton. The disease can have a profound impact on life quality in terms of physical, social and psychological well-being. It has a great detrimental effect on our social and economic stability as the disease is more severe in men than in women. Work disability in AS patients is higher than expected in the general population for both male and female. Patients with AS may incur significant medical costs which accelerate steeply with increasing loss of function (BASFI) and disease activity (BASDAI). Patients with more severe disease activity are at greater risk for developing functional disability. AS influences the subjective health of the affected person, especially the physical health related QoL. BASFI, BASDAI, BASG and pain are significantly associated with SF-36 physical and mental domains in patients with AS. Pain, fatigue and stiffness are the most commonly reported symptoms of these patients. Sleep disturbance, anxiety, depression and sexual dysfunction are other factors that significantly affect patients quality of life. Birdem Med J 2014; 4(2): 88-93